Analysis of the Problems of Learning Islamic Religious Education in Senior High Schools Regarding the Effectiveness of Learning - Nasution, Abdul Rahim; Ishak, Ishak; Mulyadi, Mulyadi; Kamrul, Kamrul; Simamora, Nuraini (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
The aim of this study is to analyze the problems that exist in the teaching and learning process of Islamic Religious Education and the factors that cause these problems to occur. Data collection focused on high school. This research uses a qualitative methods with a case study approach with data collection techniques carried out by conducting interviews and observations with Islamic religious education teachers, school principals, deputy principals for student affairs, and students at the research site. The results of the research found that learning problems occurred due to the lack of learning facilities and infrastructure in schools, such as reading books so that which had an effect on students' lack of interest in reading at school besides that there were also problems with the lack of variations in methods and models teaching Islamic Education teachers so that student learning motivation does not increase and learning is more dominant in cognitive nature so that students only understand religion but have not been able to implement it optimally in everyday life.